Chlamydia infection, pelvic inflammatory disease, ectopic pregnancy and infertility: cross-national study. Issue 7 (25th October 2011) - Bender, Nicole; Herrmann, Björn; Andersen, Berit; Hocking, Jane S; van Bergen, Jan; Morgan, Jane; van den Broek, Ingrid VF; Zwahlen, Marcel; Low, Nicola
Abstract : Objectives: To describe, using routine data in selected countries, chlamydia control activities and rates of chlamydia infection, pelvic inflammatory disease (PID), ectopic pregnancy and infertility and to compare trends in chlamydia positivity with rates of PID and ectopic pregnancy. Methods: Cross-national comparison including national data from Australia, Denmark, the Netherlands, New Zealand, Sweden and Switzerland. Routine data sources about chlamydia diagnosis and testing and International Classification of Disease-10 coded diagnoses of PID, ectopic pregnancy and infertility in women aged 15–39 years from 1999 to 2008 were described. Trends over time and relevant associations were examined using Poisson regression. Results: Opportunistic chlamydia testing was recommended in all countries except Switzerland, but target groups differed. Rates of chlamydia testing were highest in New Zealand. Chlamydia positivity was similar in all countries with available data (Denmark, New Zealand and Sweden) and increased over time. Increasing chlamydia positivity rates were associated with decreasing PID rates in Denmark and Sweden and with decreasing ectopic pregnancy rates in Denmark, New Zealand and Sweden. Ectopic pregnancy rates appeared to increase over time in 15–19-year-olds in several countries. Trends in infertility diagnoses were very variable. Conclusions: The intensity of recommendations about chlamydia control varied between countries but was not consistently related to levels of chlamydia diagnosis or testing. Relationships between levels of chlamydia infection and complication rates between or within countries over time were not straightforward. Development and validation of indicators of chlamydia-related morbidity that can be compared across countries and over time should be pursued.